Cooperation between the Buryat-Mongolian scientific committee and mongolian scientific institute in forming research libraries - Ts. P. Vanchikova; M. V. Ayusheeva (Библиосфера)
The article discusses international relations between the Buryat-Mongolian Scientific Committee (Buruckom) and Committee of Sciences of Mongolia (Mongolian Scientific Institute (Monuchcom or Sudar bichgiin khyreelen). They were the first research institutions in Mongolia and Buryatia and formed the bases of the modern Academy of Sciences of Mongolia, and the Institute for Mongolian, Buddhist and Tibetan Studies of the Siberian Branch of the Russian Academy of Sciences (IMBTS SB RAS). It is actual and quite important to study the formation history of these research institutions in general, and research departments, in particular, libraries playing a great role in the history of modern science development, in relation to their upcoming 100th anniversaries. Such researches fill in the gaps in the countries’ historical past, draw attention to national cultural traditions and are connected with the problems of preserving written historical and cultural monuments. The authors used archival documents kept in the Center of Oriental Manuscripts and Xylographs of IMBTS SB RAS to highlight the history of forming and developing the collections of Buruchkom’s Manuscript Department and Monuchkom’s Research Library. They are the correspondence of the Buryat-Mongolian Scientific Committee leaders with Monuchcom scholars, datsan councils, khoshun executive committees and lamas on the issues of xylographing Buddhist treaties and supplementing library funds stored in the archive of the Center for Oriental manuscripts and xylographies of IMBT SB RAS.